Cultural protection against traumatic stress: traditional support of children exposed to the ritual of female genital cutting - Schultz JH; Lien IL (Dove Medical Press, 2014)
Jon-Håkon Schultz, Inger-Lise Lien Norwegian Centre for Violence and Traumatic Stress Studies, Oslo, Norway Abstract: This study explores the factors addressed in folk psychology in The Gambia for protecting the girl-child from the potential traumatic stress of female genital cutting (FGC). The type and quality of the psychological care was analyzed and compared with research on traumatic stress and principles for crisis and trauma intervention. Thirty-three qualitative indepth interviews were conducted with mothers who had supervised their daughters' FGC, women who had been circumcised, and professional circumcisers. The findings indicate that the girls have largely managed to handle the potentially traumatic event of FGC. The event is placed in a meaningful system of understanding, and the stress is dealt with in a traditional way that to a great extent follows empirically-based and evidence-based principles of crisis intervention. However, the approach tends to be culturally encoded, based on the local cultural belief system. This puts circumcised individuals in a potentially vulnerable position if they are living outside the homeland's supportive cultural context, with consequences for psychological and culturally competent FGC health care in exile. Keywords: female genital cutting, traumatic stress, trauma-informed care, cultural psychology